2019
DOI: 10.3892/etm.2019.7294
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thrombelastogram-guided medication in patients with coronary heart disease after percutaneous coronary intervention

Abstract: Effects of thrombelastogram-guided (TEG-guided) clopidogrel and aspirin on major adverse cardiovascular events (MACE) after percutaneous coronary intervention (PCI) were investigated. A retrospective analysis was performed on 203 patients undergoing PCI interventional therapy in the Cardiovascular Medicine of Weihai Central Hospital from February 2015 to September 2016. The patients were treated with clopidogrel and aspirin for anti-thrombus therapy. Among them, 104 patients who had TEG detection of anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Various studies and meta-analyses have shown that monitoring platelet-fibrin clot formation with VHA can improve diagnosis, trigger goal-directed transfusion and antiplatelet therapy, and decrease surgery-related bleeding [42,124,125] In addition, platelet function testing and viscoelastic platelet function assays, when added to standard coagulation assays, demonstrated clinical importance in both surgical settings for assessing coagulopathic bleeding [41,42] cardiology settings for monitoring response to antiplatelet therapy [76], and the prediction of future ischemic events [71]. The addition of the AA-and ADP-based VHA allows platelet function to be assessed alongside coagulation dynamics, so that clinicians can determine response to therapy, and to assess the relative contribution of platelet function and coagulation dynamics, and individually schedule major surgery without increased bleeding risk [47,126].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies and meta-analyses have shown that monitoring platelet-fibrin clot formation with VHA can improve diagnosis, trigger goal-directed transfusion and antiplatelet therapy, and decrease surgery-related bleeding [42,124,125] In addition, platelet function testing and viscoelastic platelet function assays, when added to standard coagulation assays, demonstrated clinical importance in both surgical settings for assessing coagulopathic bleeding [41,42] cardiology settings for monitoring response to antiplatelet therapy [76], and the prediction of future ischemic events [71]. The addition of the AA-and ADP-based VHA allows platelet function to be assessed alongside coagulation dynamics, so that clinicians can determine response to therapy, and to assess the relative contribution of platelet function and coagulation dynamics, and individually schedule major surgery without increased bleeding risk [47,126].…”
Section: Discussionmentioning
confidence: 99%
“…VHA measurements of platelet function and hemostasis factors are demonstrated as risk predictors of ischemia and bleeding in patients undergoing percutaneous coronary intervention (PCI) [67][68][69], and have shown a correlation with disease severity in patients with cardiovascular diseases [70][71][72][73]. The addition of platelet function assays to treatment algorithms in the presence of aspirin or a P2Y 12 receptor inhibitor further allows clinicians to monitor antiplatelet therapy and individualize both the medication type and the dose [66,[74][75][76][77][78][79][80][81][82][83][84][85]. VHAs have been used to explore the efficacy and safety of antiplatelet therapies, including aspirin [64], clopidogrel [86], cangrelor [87], and the direct oral anticoagulant such as dabigatran [88].…”
Section: Interventional Cardiologymentioning
confidence: 99%
“…An inhibition of <20% is the reference normal value on platelet mapping 19 and <30% inhibition did not increase the risk of bleeding during coronary artery bypass grafting 24 . Some studies have used <30% inhibition, 25 whereas others have used <50% inhibition to define clopidogrel resistance 19,26 . A review of percentage platelet aggregation of patients with and without ischemic events within 1 year as measured by 2‐µmol/l ADP‐induced thromboelastography in those undergoing nonemergent coronary stent placement was performed 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, none have been accepted as standard tools due to the variability between individuals and the poor correlation between these devices. The antiplatelet resistance mechanism is not fully understood; it is multifactorial, involving dynamic pharmacology, kinetic drug pharmacology, and genetic polymorphisms (Bonello et al, 2010;Hidayati et al, 2017;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%